2021
DOI: 10.1002/hep4.1851
|View full text |Cite
|
Sign up to set email alerts
|

Dysmetabolism, Diabetes and Clinical Outcomes in Patients Cured of Chronic Hepatitis C: A Real‐Life Cohort Study

Abstract: The aim of this study was to examine the impact of features of dysmetabolism on liver disease severity, evolution, and clinical outcomes in a real‐life cohort of patients treated with direct acting antivirals for chronic hepatitis C virus (HCV) infection. To this end, we considered 7,007 patients treated between 2014 and 2018, 65.3% with advanced fibrosis, of whom 97.7% achieved viral eradication (NAVIGATORE‐Lombardia registry). In a subset (n = 748), liver stiffness measurement (LSM) was available at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Populationbased studies over the past two decades have shown that diabetes is an independent metabolic risk factor for HCC and mortality, both in the general population, 29 and in chronic viral hepatitis patients. 30,31 Furthermore, there is growing evidence that diabetes increases risk of HCC in the presence of fatty liver. In a large cohort study that investigated the effects of metabolic traits (ie, diabetes, hypertension, dyslipidemia and obesity) on risk of HCC among 271 906 NAFLD patients, diabetes was the only significant independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populationbased studies over the past two decades have shown that diabetes is an independent metabolic risk factor for HCC and mortality, both in the general population, 29 and in chronic viral hepatitis patients. 30,31 Furthermore, there is growing evidence that diabetes increases risk of HCC in the presence of fatty liver. In a large cohort study that investigated the effects of metabolic traits (ie, diabetes, hypertension, dyslipidemia and obesity) on risk of HCC among 271 906 NAFLD patients, diabetes was the only significant independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that among the MAFLD diagnostic criteria, diabetes is the only criterion that can independently identify chronic viral hepatitis patients at high risk of HCC and mortality. Population‐based studies over the past two decades have shown that diabetes is an independent metabolic risk factor for HCC and mortality, both in the general population, 29 and in chronic viral hepatitis patients 30,31 . Furthermore, there is growing evidence that diabetes increases risk of HCC in the presence of fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…All in all, evidence suggests that in patients with advanced HCV cured with DAAs, HCC risk stratification based on MD and even more in the presence of diabetes, rather than US, should be used together with additional non‐invasive biomarkers 14 to guide reinforced HCC surveillance by, for example, magnetic resonance imaging, including with abbreviated protocols, in high‐risk patients 42,43 . In addition, pharmacological approaches targeting metabolic co‐morbidities, such as metformin in patients with diabetes or fasting hyperglycaemia but without decompensated cirrhosis, may decrease HCC incidence 15,44 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined the consequences of applying the MD diagnostic criteria derived from the MAFLD definition in a real‐life cohort of patients with advanced hepatitis C who were cured with direct antiviral agents. We took advantage of the NAVIGATORE‐Lombardia cohort, a real‐world cohort representative of a large European region, where data related to metabolic co‐morbidities were collected in order to assess their impact on the main clinical events after antiviral treatment, namely HCC and CVE 15 . In this cohort, we confirmed a role of older age and male sex in predisposing to the development of de novo HCC after achieving a sustained virological response, as we previously reported in the overall population, including patients with less advanced fibrosis, co‐infected with HCV/HIV or transplanted 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation